Differentiated Instruction Management for Enhancing Student Well-Being in Unggulan Aisyiyah Bantul Primary School - Jannah, Mailatul; Maryani, Ika; Santosa, Achadi Budi; Okimustava, Okimustava; Shaafi, Nur Farha (Universitas Muhammadiyah Surakarta, 2026)
Unggulan Aisyiyah Primary School, as a flagship Sekolah Penggerak in Bantul Regency, has consistently implemented differentiated instruction within the Merdeka Curriculum. However, while previous studies have widely examined differentiated instruction as a teaching strategy, limited research has focused on how it is managed systematically to foster student well-being in primary schools. This study addresses this gap by asking: How is differentiated instruction managed to enhance student well-being in a primary school context? The objective is to formulate a contextual management model that supports students’ cognitive, social, and emotional well-being. A descriptive qualitative approach was used, involving interviews with the principal, the vice principal for curriculum, two fourth-grade teachers, and two students, complemented by classroom observations and document analysis. Data were analyzed using thematic analysis procedures, including coding, theme development, and interpretation. The findings reveal that differentiated instruction management aligns with Tomlinson’s framework and encompasses four components: planning, organizing, implementation, and supervision. Planning involves identifying student needs and collaborative module preparation through team teaching. Organizing focuses on flexible grouping and creating a positive learning environment. Implementation uses multi-method and multi-source instructional strategies tailored to student profiles. Supervision is conducted through coaching, counseling, and mentoring to ensure continuous improvement. This model highlights that effective differentiated instruction management can enhance student engagement, social interaction, and emotional security, thus strengthening student well-being. Strengthening implementation requires practical guidelines, sustained mentoring, time management, and collaboration with psychological support professionals.